2000
DOI: 10.4141/s99-045
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying short-term effects of crop rotations on soil organic carbon in southwestern Saskatchewan

Abstract: . 2000. Quantifying short-term effects of crop rotations on soil organic carbon in southwestern Saskatchewan. . Crop management practices can have a major influence on soil fertility and soil organic C (SOC) sequestration. We need to accurately measure and estimate changes in SOC in the short term (<20 yr). A 10-yr crop rotation experiment, conducted on a medium-textured Orthic Brown Chernozem at Swift Current, in southwestern Saskatchewan, was sampled in 1990 (3 yr after initiation of the study) and in 1993 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
2
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 19 publications
2
65
2
1
Order By: Relevance
“…This experiment has been described in detail previously (Zentner et al 2003(Zentner et al , 2004(Zentner et al , 2006Campbell et al 2000b); thus, we present only a brief description of the techniques used, and additional information and data specific to the objectives of this paper.…”
Section: Experimental Datamentioning
confidence: 99%
See 2 more Smart Citations
“…This experiment has been described in detail previously (Zentner et al 2003(Zentner et al , 2004(Zentner et al , 2006Campbell et al 2000b); thus, we present only a brief description of the techniques used, and additional information and data specific to the objectives of this paper.…”
Section: Experimental Datamentioning
confidence: 99%
“…However, we measured bulk densities in the fall of 1996 and, assuming that density had not changed since 1990, we used the 1996 values to convert SOC concentrations to mass for 1990and 1996(Campbell et al 2000b. Because bulk density in the 7.5-to 15-cm depth was generally constant among all treatments (average 1.39 Mg m -3 ), we used this mean value to estimate the SOC mass for this segment.…”
Section: Monitoring Soil Organic Carbonmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, if the lentil was the reason for the under-estimation, the difference between measured and estimated values should be diverging over time with more cycles of the legume-containing system, but this has not happened. Campbell et al (1995Campbell et al ( , 2000b have shown that, because of the large spatial variability that often exists, even on landscapes that are level and uniform looking, accurate quantification of C changes requires that repeated measurements be made in the same plots over time. Assumptions that SOC is constant in contiguous areas of a field can lead to large discrepancies (Campbell et al , 2000b.…”
Section: Estimating Soc Using Equationmentioning
confidence: 99%
“…Campbell et al (1995Campbell et al ( , 2000b have shown that, because of the large spatial variability that often exists, even on landscapes that are level and uniform looking, accurate quantification of C changes requires that repeated measurements be made in the same plots over time. Assumptions that SOC is constant in contiguous areas of a field can lead to large discrepancies (Campbell et al , 2000b. However, if initial measurements are not available we are often left with little choice but to make assumptions and hope for the best.…”
Section: Estimating Soc Using Equationmentioning
confidence: 99%